Makna Diri dan Branding Fotografer - Yogascitra Naufal; Neni Yulianita; Anne Maryani (KOMVERSAL, 2023)
The development of photography in the city of Bandung is closely related to the development of photography in Indonesia. Bandung is one of the big cities in Indonesia with a very rapid development of photography, especially with the emergence of various photographers with specialization in their fields. With the presence of many photographers who have started to appear in the city of Bandung, many photographers are still looking for the meaning of their photography activities and the branding that must be done so that the public becomes aware and uses their services. From this phenomenon, the research "Self Meaning and Photographer Branding" was created. This study uses a qualitative research method with a phenomenological study approach from Alfred Schutz. The purpose of this study is to find out, describe and analyze the motives of photographers in the city of Bandung in carrying out photography activities, to analyze and identify the experiences of photographers in the city of Bandung in carrying out photography activities, to find and describe the self-meanings of photographers in the city. Bandung in photography activities and to identify and describe the branding of photographers in the city of Bandung to attract consumer interest. This research uses social action theory from Max Webber. This research produces the because motive and in order to motive owned by the photographers, there are eleven motives owned by the photographers, namely, hobbies, love, environment, campaigns, earning a living, role models, visualization of imagination, remembering stories, appreciation, improvement confidence and dreams. The experience gained by photographers in the city of Bandung in carrying out photography activities is divided into three aspects, namely, obstacles, satisfaction and achievements. The meaning obtained by photographers in the city of Bandung in photographic activities is divided into three aspects, namely, the purpose, sensation and character of the photo. Branding carried out by photographers in the city of Bandung is obtained through three strategies namely, through social media, word of mouth and through the community.